تغيرات عرض الحنك والقوس السنية العلوية عند مرضى الصنف الثاني النموذج الأول المعالجين بقلع الضواحك الأولى العلوية - حسن, حازم; سعد, رامي (Latakia University Journal -Medical Sciences Series, 2018)
هدف البحث: كان الهدف من هذه الدراسة تقييم التغيرات في عرض الحنك والقوس السنية العلوية خلال المعالجة التقويمية بالأجهزة الثابتة مسبقة البرمجة (MBT) مع قلع الضواحك الأولى العلوية عند مرضى الصنف الثاني النموذج الأول من سوء الإطباق. المواد والطرق: أجريت القياسات على الأمثلة الجبسية عند 24 مريض صنف ثاني نموذج أول (16 أنثى و8 ذكور). كان الحد الأدنى لعمر أفراد العينة 16 عام فما فوق، بعمر وسطي 20.29 ± 2.82 سنة. تمت معالجة جميع المرضى بالأجهزة الثابتة (نظام MBT) مع قلع الضواحك الأولى العلوية. تم قياس العرض السني والعرض الحنكي (بين النابي والعرض بين الرحوي) باستخدام مسماك الكتروني بدقة 0.01. تم تطبيق التحليل الاحصائي t-test للعينات المرتبطة لتقييم التغيرات في القيم قبل وبعد المعالجة عند العينة كاملة وعند كل من مجموعة الذكور ومجموعة الإناث، كما تم تقييم الفروق بين الإناث والذكور باستخدام تحليل t-test للعينات المستقلة. النتائج: لوحظ ازدياد كل من العرض السني والحنكي بين النابي بشكل هام احصائياً مع نهاية المعالجة (P>0.001). كما لوحظ ازدياد العرض السني بين الرحوي إلا أن هذه الزيادة لم تكن هامة احصائيا (P<0.05). كذلك ازداد العرض الحنكي بين الرحوي بشكل هام احصائياً (P>0.001). لم يلاحظ أي اختلافات هامة احصائياً بين الذكور والإناث. الخلاصة: هناك ميل واضح لازدياد الأبعاد العرضية للحنك والقوس السنية العلوية عند مرضى الصنف الثاني النموذج الأول المعالجين بقلع الضواحك الأولى العلوية باستثناء العرض السني بين الرحوي. يجب أن تأخذ الدراسات المستقبلية بعين الاعتبار شكل القوس قبل التداخل العلاجي والعوامل المرتبطة بالدعم. Objective: The aim of this study was to determine palatal and maxillary arch width changes during MBT PEA with maxillary first premolars extraction treatment in patients with Class II division 1 malocclusion. Material and Methods: Dental casts of 24 Class II division 1 patients (8 males and 16 females) were evaluated. The minimum age of the subjects at the beginning of treatment was above 16 years with mean age ±20.29 2.82. All patients were treated with extraction of the maxillary first premolars and MBT PEA. Pre- and post-treatment maxillary and palatal (inter-canine and inter-molar) widths were measured using a digital calliper of 0.01 accuracy. Paired samples t-test was used to evaluate the treatment changes within total sample and within males group and females group. Differences between males and females were tested using independent samples t-test. Results: At the end of treatment, maxillary and palatal inter-canine widths increased significantly (P>0.001).The maxillary inter-molar width increased but the values were statistically insignificant (P<0.05). The palatal inter-molar width increased significantly (P>0.01). No significant differences were observed between males and females. Conclusions: Class II division 1 patients treated with extraction of maxillary first premolars had tendency for an increase in palatal and arch width during treatment except maxillary inter-molar width. It seems that a more thorough assessment and investigation including pretreatment arch shape and factors related to anchorage should be carried out.